Uncovering the US term premium: An alternative route - Gil-Alana, Luis A.; Moreno, Antonio (Journal of Banking & Finance, 2012)
The estimates of the US term premium crucially depend upon the ex-ante decision on whether the short-term rate is either an I(0) or an I(1) process. In this paper we estimate a fractionally integrated (I(d)) model which simultaneously determines both the order of integration of the short-term rate and the associated term premium. We show that the term premium experienced a sharp increase from essentially zero in mid-2007 to almost 3% in 2009. We also show that unemployment and term premium dynamics exhibit a very significant positive co-movement.